Clonal Variation in Regeneration of Shoots after Hedging in Vegetative Multiplication Garden of Dalbergia sissoo (Shisham) Roxb. - Bakshi, Meena; Thakur, K. S.; Kumar, Surinder (Indian Forester, 2007)
Ninety six clones of Dalbergia sissoo were hedged at 30 cm of height level in the month of Jan. - Feb. in VMG at Birplasi, Nalagarh (HP) to assess shoot regeneration capacity of different clones. Significant differences (P> 0.001) were observed among clones regarding days to shoot emergence, collar diameter of cut stumps, shoot number, shoot length and basal diameter of shoots. The earliest shoot emergence (5 days) was recorded in clone 86 and 91 both belonging to Rajasthan. The maximum number of shoots (67) were recorded in clone 107 (Rajasthan) followed by 57 shoots (Clone 42, Gonda), while maximum shoot length (133cm) and diameter (11 mm) was observed in clone 9 (Pathri, Haridwar). A feeble (r=0.68) correlation was observed between collar diameter of stump and number of regenerated shoots.